Formation of Massive and Wide First-star Binaries in Radiation Hydrodynamic Simulations - Kazuyuki Sugimura; Tomoaki Matsumoto; Takashi Hosokawa; Shingo Hirano; Kazuyuki Omukai (The Astrophysical Journal, 2023)
We study the formation of Population III stars by performing radiation hydrodynamic simulations for three different initial clouds extracted from cosmological hydrodynamic simulations. Starting from the cloud collapse stage, we follow the growth of protostars by accretion for ∼10 ^5 yr until the radiative feedback from the protostars suppresses the accretion and the stellar properties are nearly fixed. We find that Population III stars form in massive and wide binary/small-multiple stellar systems, with masses >30 M _⊙ and separations >2000 au. We also find that the properties of the final stellar system correlate with those of the initial clouds: the total mass increases with the cloud-scale accretion rate, and the angular momentum of the binary orbit matches that of the initial cloud. While the total mass of the system in our simulations is consistent with our previous single-star formation simulations, individual masses are lower due to mass sharing, suggesting potential modification in the extent of feedback from Population III stars in the subsequent evolution of the Universe. We also identify such systems as mini-binaries embedded in a wider outer multiple-star system, which could evolve into progenitors for observed gravitational wave events.